Application of the Simple Additive Weighting Method in the Selection Process for Recipients of the 1000 Anak Negeri Scholarship at Nusa Putra University - Rahmat Hidayat; Gandung Triyono; Dara Putri Oktiara (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
The 1000 Anak Negeri Scholarship at Nusa Putra University supports outstanding students from underprivileged families, yet its manual selection process is inefficient, subjective, and lacks transparency, leading to delays and potential misjudgments. This study aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to enhance the accuracy, efficiency, and fairness of scholarship selection. The system evaluates applicants based on eight criteria: poverty status, parental occupation, income, family dependents, parental status, academic achievement, non-academic achievement, and Quran recitation ability, with assigned weights ensuring objective ranking. The SAW method normalizes decision matrices and calculates final scores to determine recipients, significantly improving efficiency and transparency compared to manual selection. The top-ranked recipient achieved a final score of 0.7765, followed by scores of 0.743, 0.625, 0.6105, and 0.584, demonstrating a more structured and reliable selection process. The automated approach reduces processing time, minimizes human errors, and ensures systematic selection based on predefined criteria. This research confirms that the SAW method provides a more accurate and reliable decision-making process, making scholarship distribution fairer and more targeted. The implementation of this system at Nusa Putra University serves as a model for other educational institutions to optimize their scholarship selection processes, ensuring that financial aid reaches students who need it most while improving transparency, efficiency, and decision-making accuracy.